2015
DOI: 10.3390/molecules20058759
|View full text |Cite
|
Sign up to set email alerts
|

Development and Characterization of Transcription Factor Gene-Derived Microsatellite (TFGM) Markers in Medicago truncatula and Their Transferability in Leguminous and Non-Leguminous Species

Abstract: Transcription factors (TFs) are critical adaptor molecules that regulate many plant processes by controlling gene expression. The recent increase in the availability of TF data has made TFs a valuable resource for genic functional microsatellite marker development. In the present study, we developed TF gene-derived microsatellite (TFGM) markers for Medicago truncatula and assessed their cross-species transferability. A total of 203 SSRs were identified from 1467 M. truncatula TF coding sequences, 87.68% of whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2
2
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 29 publications
4
16
0
Order By: Relevance
“…One hundred twenty-six (74.56%) of the 169 assayed Mt-mi-RNA-SSR markers provided consistent amplification in alfalfa ( Table 2). This result agrees with the previous study that high transferability possessed by the microsatellite markers developed from M. truncatula in alfalfa (85.21%) [34]. We further analyzed the transferability of these 169 Mt-mi-RNA-SSR markers in other five leguminous species, and high transferability also has been identified, such as 77.51% in Glycine max, 89.35% in Vicia sativa, 88.76% in Melilotus, 90.53% in Lotus corniculatus, and 89.…”
Section: Transferability Of Mt-mi-rna-ssr Markers In Leguminous Speciessupporting
confidence: 94%
See 1 more Smart Citation
“…One hundred twenty-six (74.56%) of the 169 assayed Mt-mi-RNA-SSR markers provided consistent amplification in alfalfa ( Table 2). This result agrees with the previous study that high transferability possessed by the microsatellite markers developed from M. truncatula in alfalfa (85.21%) [34]. We further analyzed the transferability of these 169 Mt-mi-RNA-SSR markers in other five leguminous species, and high transferability also has been identified, such as 77.51% in Glycine max, 89.35% in Vicia sativa, 88.76% in Melilotus, 90.53% in Lotus corniculatus, and 89.…”
Section: Transferability Of Mt-mi-rna-ssr Markers In Leguminous Speciessupporting
confidence: 94%
“…Chromosomes 3 and 4 contained the largest number of markers (35, 21.08%), while the fewest mapped on chromosome 1 (8, 4.82%) ( Figure 1). Previously, 4636 EST-SSR markers [33] and 130 transcription factor gene-derived SSR markers had been developed from M. truncatula based on 3828 EST sequences and 176 transcription factor sequences, respectively [34]. To determine the novelty of the 169 Mt-miRNA-SSR markers developed in this study, the 130 SSR-containing pri-miRNA sequences were cross-referenced with the 3828 EST sequences and 176 transcription factor sequences, respectively.…”
Section: Development Of Mt-mirna-ssr Markersmentioning
confidence: 99%
“…Targeted TFs could be utilized for developing next generation microsatellites, Transcription Factor Gene-Derived Microsatellite (TFGM) Markers which have potential in marker-assisted genetic improvement and genotyping applications through marker assisted selection (MAS) breeding program to develop the drought/heat responsive and nutrient efficient cultivars for cereal crops (Gupta and Prasad, 2009; Kujur et al 2013, 2014; Liu et al 2015). However in plants, (TFGM) markers have only been reported in chickpea and Medicago truncatula to date (Kujur et al 2013; Liu et al 2015).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, in silico development of genic and EST-SSR markers can now be relatively easily done using publicly available nucleotide sequence databases. Genic SSRs in functional genes can be used as "functional genetic markers", and they have a much higher transferability across different taxa than random genomic SSRs [38]. Sargent et al [39] used primer pairs based on the binding sites in the Fragaria exons flanking polymorphic introns and found that their transferability was significantly higher compared to the random genomic SSRs.…”
Section: Discussionmentioning
confidence: 99%